LEGAL DISCRETION AND STATE RESPONSIBILITY TO REALIZE POLITICAL HUMAN RIGHTS LAW FOR FOREIGNERS WITHOUT DOCUMENTS - Valent Pontororing; Ronald Mawuntu; Jemmy Sondakh; Caecilia Waha (Journal of the Community Development in Asia (JCDA), 2022)
The population living without documents in Indonesia continues to grow from year to year. Law No. 12 of 2006 concerning Citizenship and Immigration Law. Number has not provided a solution regarding their residence permit status and citizenship.Problems that arise the number of people who are settlers without documents increases, especially if they have mixed marriages with Indonesians. The handling so far that has been carried out by the government is only unclear and tends to ignore the problem of how the state's discretion and responsibility towards foreign citizens are without documents. By using normative research methods, research is carried out. The results of the study a. the immigration office's discretion regarding the status of foreigners without documents is unclear. b. The state is not responsible for the status and existence of foreign citizens without documents by neglecting their civil rights status c. Politics of protecting human rights against foreign nationals without documents are unclear until now. Keywords: Foreign Citizens Without Documents, Discretion, and Immigration